VISUALIZATION OF BATIK LATOHAN MOTIF IN LASEM DISTRICT, REMBANG REGENCY - Qisthi Maghfiroh; Edi Kurniadi; Mulyanto Mulyanto (Proceeding of International Conference on Art, Language, and Culture, 2017)
Batik is a blend of art on cloth by using traditional malam coating techniques, which create its own uniqueness that causes batik is recognized by the world since October 2, 2009. In its development, batik art is no longer only done and developed in the palace environment, but also began to work and grow outside the palace to the coastal area. This can be seen with the emergence of batik artisans coming from outside the palace, such as in the Lasem (Rembang), Pekalongan, Tuban, Cirebon, Demak, and other areas with the characteristics and uniqueness of each, and the creativity of batik craftsmen itself. Widespread and developed batik, encouraging the birth of new motifs that have its own characteristics in each region, especially in Lasem. This research tries to explain the visualization of batik latohan motif in Lasem District, Rembang Regency. Methods of data collection are interviews, observation and documentation. The validity of the data using Miles technics of data triangulation. Finding that: (1) Latohan motif obtained and inspired from the depiction of plants latoh, which is a kind of seaweed that became typical food coastal communities, especially Lasem; (2) Visualization of batik latohan motif using plant ornaments that are given isen-isen that make the motif appear more volume, life, and rhythm, and combined with the game of good and beautiful color, so happened color effect with special style of Lasem batik.